Do managers define non-GAAP earnings to meet or beat analyst forecasts? - Doyle, Jeffrey T.; Jennings, Jared N.; Soliman, Mark T. (Journal of Accounting and Economics, 2013)
We provide evidence consistent with firm managers opportunistically defining non-GAAP earnings in order to meet or beat analyst expectations. This result is robust to controlling for other tools of benchmark beating (e.g., discretionary accruals, real earnings management, and expectation management). We also find that managers tend to exclude more expenses from non-GAAP earnings when it is costlier to use accrual earnings management due to balance sheet constraints, indicating that these tools are substitutes. Lastly, we find that investors discount positive earnings surprises when accompanied by exclusions from GAAP earnings, suggesting that the market partially understands the opportunistic nature of these exclusions. Our evidence is consistent with managers opportunistically defining non-GAAP earnings in a way that analysts fail to fully anticipate, resulting in an increased likelihood of exceeding analyst forecasts.